Formulação e análise de creme clareador a partir do suco da pêra e seus componentes - JESUS, Aghata F. de; MACEDO, Ana Júlia; ANDRADE, Danielly L. de; NASCIMENTO, Erick O. (244, 2023)
Quando aplicado sobre a pele, o ácido málico promove a redução dos sinais de idade, a remoção de células mortas, é usado no tratamento da acne, mantém a pele hidratada, com aparência jovem e firme e pode reverter o aparecimento de manchas na pele provocadas pela luz solar. Este trabalho teve como objetivo realizar a formulação de um creme clareador composto com suco da pêra que contém o ácido málico. A extração do ácido se deu através da maceração do fruto in natura que compôs a formulação do creme clareador. As análises fisicoquímicos e organolépticos tiveram resultados satisfatórios, mantendo os parâmetros dentro dos permitidos pela ANVISA (Agência Nacional de Vigilância Sanitária). A emulsão formada apresentou textura homogênea e consistente e de fácil aplicação

When applied to the skin, malic acid promotes the reduction of signs of aging, the removal of dead cells (used in whitening treatments), in addition to being used to treat acne. Furthermore, it keeps the skin hydrated and, consequently, its youthful and firm appearance. Furthermore, this acid is also linked to the production of collagen in the body. Therefore, it helps maintain skin firmness, and can also reverse the appearance of skin blemishes caused by sunlight. This work aimed to formulate a whitening cream composed of pear juice, which contains malic acid and other components, extracted through maceration, filtration and finally the formulation of the whitening cream. After these previously mentioned processes, physical-chemical and organoleptic analyzes were carried out, where the results obtained fit the parameters imposed by the National Health Surveillance Agency (ANVISA). The cream presented a homogeneous and consistent texture, visually comparable to commercial whitening products, in addition to forming a stable emulsion with good dispersion of essence when they were added.
Keywords: Química; Creme; Produção Industrial